(untitled) (Development Service Industry Management, 2024)
In the context of modern environmental challenges, such as climate change, land degradation, water resource pollution, ensuring environmental safety is becoming one of the priorities for the development of agrarian business. Subjects of agricultural activity that actively use natural resources must responsibly approach environmental issues, ensuring minimal impact on the environment. Environmental safety of an enterprise is an important aspect of its activities, which involves protecting the environment from the negative impact of production processes. Assessment of environmental safety is possible through a system of indicators that allow identifying, analyzing and controlling environmental risks. This report examines the main groups of indicators that describe the environmental safety of an enterprise. It is determined that the environmental safety of an enterprise can be assessed using various groups of indicators that reflect the environmental, economic and social aspects of activity. Their systematic analysis is the basis for developing effective environmental strategies and maintaining the competitiveness of an enterprise in the context of growing attention to sustainable development. It is noted that environmental and economic security are complementary components of the successful functioning of a business entity. Ensuring harmony between them contributes to increasing the efficiency of activities, conserving resources and maintaining the long-term competitiveness of the enterprise. Based on the research conducted, it can be concluded that ensuring the environmental security of agrarian business entities requires a systematic approach, which includes risk analysis, the use of innovative technologies and compliance with environmental standards. It is recommended to implement monitoring systems, use environmentally friendly technologies and integrate sustainable development strategies into enterprise management. The introduction of modern conceptual approaches and assessment methods allows minimizing the negative impact on the environment, optimizing the use of resources and promoting environmental responsibility.